2023
DOI: 10.1186/s40035-023-00392-8
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson’s disease and gut microbiota: from clinical to mechanistic and therapeutic studies

Xuxiang Zhang,
Beisha Tang,
Jifeng Guo

Abstract: Parkinson’s disease (PD) is one of the most prevalent neurodegenerative diseases. The typical symptomatology of PD includes motor symptoms; however, a range of nonmotor symptoms, such as intestinal issues, usually occur before the motor symptoms. Various microorganisms inhabiting the gastrointestinal tract can profoundly influence the physiopathology of the central nervous system through neurological, endocrine, and immune system pathways involved in the microbiota–gut–brain axis. In addition, extensive eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 309 publications
0
16
0
Order By: Relevance
“…Besides, emerging research suggested a connection between the gut microbiome and neurodegenerative conditions like Parkinson’s disease. Changes in the gut microbiome composition might influence the development and progression of neurodegenerative diseases through the gut-brain axis ( Zhu et al, 2021 ; Zhang et al, 2023a ). From a similar perspective, this study analyzed the impact of the non-cutaneous microbial environment on hypertrophic scarring.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, emerging research suggested a connection between the gut microbiome and neurodegenerative conditions like Parkinson’s disease. Changes in the gut microbiome composition might influence the development and progression of neurodegenerative diseases through the gut-brain axis ( Zhu et al, 2021 ; Zhang et al, 2023a ). From a similar perspective, this study analyzed the impact of the non-cutaneous microbial environment on hypertrophic scarring.…”
Section: Discussionmentioning
confidence: 99%
“…10. 3389/fmicb.2024.1345717 Frontiers in Microbiology 07 frontiersin.org through the gut-brain axis (Zhu et al, 2021;Zhang et al, 2023a). From a similar perspective, this study analyzed the impact of the non-cutaneous microbial environment on hypertrophic scarring.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have linked gut microbiota imbalance to the development of PD, where dysbiosis increases gut permeability, enabling harmful substances to trigger inflammation. Activation of immune cells by microbial products releases inflammatory molecules that damage dopaminergic neurons through neuroinflammation, facilitated by the vagus nerve (Zhang X. et al, 2023).…”
Section: Parkinson's Diseasementioning
confidence: 99%
“…20−24 Besides this, microbial treatment has also drawn interest lately for its potential in alleviating PD disease symptoms. 25 Administration of gut microenvironment modifying agents may afford neuroprotection by regulating the gut−brain axis, controlling gut dysbiosis. Probiotic supplementation containing a variety of microbes can effectively alleviate symptoms of PD by addressing various cellular and molecular processes such as oxidative stress, apoptosis, and inflammatory and anti-inflammatory pathways.…”
Section: Introductionmentioning
confidence: 99%